An economic model of the Los Olivitos mangrove ecosystem in Venezuela - G í¶ran M í¤ler, Karl; Aniyar, Sara; Casler, Clark; Weir, Enrique; Fuenmayor, Judith; Rojas, José; Reyes, Jeny (Boletín del Centro de Investigaciones Biológicas, 1970)
An economic model that will allow us to analyze different management options for the Los Olivitos mangrove ecosystem, in western Venezuela, is presented. A basic economic problem behind any ecosystem management decision is the allocation of natural resources. It is a matter of making the appropriate “trade-off” between preservation and changes in resource uses. This trade-off requires a value analysis of the variable functions and goods provided by the wetland. The model takes into account the ecological knowledge presently available: and considers eight ecosystem features: S1 = the current stock of mangrove (mangrove biomass), S2 = the fish stock, S3 = a vector which describes all the Los Olivitos characteristics eventually attracting tourists. S4 = carbon sequestration mangrove service, S5 = nutrient stock, S6 = salinity, S7, biodiversity, and A = are above sea level. The different components of the economic value of the ecosystem will be estimated via eight equations.